On the taxonomy of water mites (Acari: Hydrachnidia) described from the Palaearctic, part 1: Hydrachnidae, Limnocharidae and Eylaidae - Davids, Kees; Sabatino, Antonio Di; Gerecke, Reinhard; Gledhill, Terence; Smit, Harry (Zootaxa, 2005)
This paper collects taxonomic changes in the families Hydrachnidae, Limnocharidae and Eylaidae which become necessary following revision of material from museum collections and recent field work. The following synonyms are established: Family Hydrachnidae, genus Hydrachna: The subgenera Anohydrachna Thor, 1916, Diplohydrachna Thor, 1916, Rhabdohydrachna K. Viets, 1931 are synonyms of Hydrachna s.str.; H. globosa neumani Lundblad, 1962a, and H. globosa rotundata Láska, 1964, are synonyms of H. globosa (De Geer, 1778); H. halberti Soar, 1908, H. levis Williamson, 1913 and H. levis acuminata K.O. Viets, 1954 are synonyms of H. incisa Halbert, 1903; H. perpera Koenike, 1908 is a synonym of H. processifera Koenike, 1903; H. skorikowi integra K. Viets, 1930 is a synonym of H. schneideri Koenike, 1895. Family Eylaidae, genus E ylais: E. bisinuosa nodipons K. Viets, 1919 is a synonym of E. bisinuosa Piersig, 1899; E. rimosa proceripalpis K. Viets, 1930 is a synonym of E. mutila Koenike, 1897; E. puripons K.Viets, 1930, E. bisinuosa oligotricha Lundblad, 1936, E. planipons novata K. Viets 1942 and E. canariensis Lundblad, 1962b are synonyms of E. planipons Walter, 1924. The following species must be regarded species incertae: Family Hydrachnidae, genus Hydrachna: H. aspratilis Koenike, 1897, H. bivirgulata Piersig, 1897a, H. brehmi Szalay, 1955, H. denudata Piersig, 1896, H. inermis Piersig, 1895, H. levigata Koenike, 1897, H. papilligera K. Viets, 1919, H. piersigi Koenike, 1897, H. regulifera Koenike, 1908, H. williamsoni Soar, 1908. Family Eylaidae, Eylais glubokensis Udalzov, 1907. The geographical origin of Hydrachna extorris Koenike, 1897, probably collected outside Europe, is unclear.